PENGETAHUAN DAN PERILAKU PERAWAT DALAM PENGGUNAAN MODERN DRESSING - Hardyanti, Meri; Pratama, Kharisma; Usman (Literasi Intelektual, 2025)
Background: Wounds are broadly defined as any tissue damage or disruption caused by physical or mechanical factors, chemicals, radiation, or temperature. One of the primary responsibilities of nurses is to facilitate the wound healing process through appropriate wound care. Modern wound dressing techniques involve closed wound management while maintaining moisture to accelerate healing, promote new tissue growth, and prevent infection. Adequate knowledge of wound care procedures enhances the effectiveness and efficiency of treatment. Furthermore, nurses who demonstrate positive attitudes toward patients can provide gentle and compassionate care, making patients feel more comfortable and supporting faster recovery. Objective: This study aims to determine the relationship between nurses’ knowledge and their behavior regarding the use of modern wound dressing at Tk.II Kartika Husada Hospital, Pontianak. Methods: This quantitative, correlational analytical study used a cross-sectional design. The population consisted of all 78 nurses working in the inpatient wards at Tk.II Kartika Husada Hospital. A total of 44 nurses were selected as samples using purposive sampling. Data were collected through questionnaires assessing knowledge and behavior and analyzed using the Fisher Exact Test. Results: The findings revealed that 29 nurses (65.9%) had a sufficient level of knowledge regarding modern dressings, while 28 nurses (63.6%) demonstrated appropriate behavior in performing modern wound care based on Standard Operating Procedures (SOPs). Conclusion: There is a significant relationship between knowledge and behavior in the use of modern dressing among nurses at Tk.II Kartika Husada Hospital, Pontianak, as indicated by a p-value of 0.000 < α (0.05).